FUNGSI KESENIAN BELUK PADA MASYARAKAT ADAT KASEPUHAN CICARUCUB - Rita Tila (LP2M ISBI Bandung, 2023)
Beluk from the Indigenous People of Kasepuhan Cicarucub are still maintained by the community based on their beliefs. The purpose of this research is to find out how the situation, events and functions of Beluk by the community in preserving their culture. In this study, the authors use the ethnographic theory of communication put forward by Dell Hymes. The method used in this research is qualitative with an ethnographic communication approach. Data collection techniques through interviews and document observation. To determine the informants used non-random sampling technique, namely purposive sampling. The data validity test technique used is the data triangulation technique which consists of interviews, observation and documentation. The data analysis technique used is to describe the findings in detail from the interpretation results, then draw conclusions on the research results obtained. The conclusion is that Beluk art has a purpose for education, morals and manners. The function of outs and outs in the traditional Kasepuhan Cicarucub community is a religious function, a social function and an entertainment function. Keywords: Function, Outline Art, Kasepuhan Cicarucub Indigenous People